A study on basic investigation and deterioration evaluation standard in water distribution network - Kong, Myeongsik; Lee, Hyundong; Kwak, Pilljae (International Journal of Engineering and Technology, 2018)
There must be a reliable evaluation to collect correct data on the factors that affect pipe performance and to analyze the acquired data to upgrade the old water distribution network effectively. This study developed a procedure for collecting the data (basic investigation) of a water distribution network and evaluating deterioration using the acquired data. The basic investigation of the water distribution network is divided into routine investigation and accident investigation. It is a process consisting of setting up investigation areas, collecting background information, and examining 23 data sets (9 indirect data sets, 4 endoscope data sets, and 10 shell data sets) needed to evaluate the facilities technically. We then calculated the score for each data item and the overall score for each evaluation step to evaluate structural problems, hydraulic problems, leakage through joints, and water quality problems to assess the deterioration of the investigated facility accurately.Â